Circulating MicroRNAs As Prognostic Biomarkers In Pediatric Hematologic Malignancies: A Systematic Review And Meta-Analysis (The Review of Diabetic Studies, 2026)
Circulating microRNAs (miRNAs) are stable, minimally invasive biomarkers with potential prognostic value in pediatric hematologic malignancies; however, evidence is fragmented and inconsistently reported. To systematically review and meta-analyze the prognostic performance of circulating miRNAs in pediatric/AYA hematologic malignancies over the last 15 years.PubMed/MEDLINE, Scopus, Web of Science, and Embase were searched, with supplementary citation chasing and targeted Google Scholar searching. Studies enrolling pediatric/AYA patients with hematologic malignancies and measuring circulating miRNAs (serum/plasma/whole blood) with survival outcomes (OS/EFS/DFS/RFS or related time-to-event outcomes) were eligible. Two reviewers screened records and extracted data. Hazard ratios (HRs) were pooled using random-effects models with direction standardized so HR > 1 indicated worse prognosis. When HRs were reported without CIs but accompanied by two-sided p-values, SEs were approximated from the z-statistic. Of 2,718 records, 15 studies met inclusion criteria for qualitative synthesis and 5 provided sufficient data for meta-analysis. Included studies were predominantly AML (11/15), with fewer ALL (3/15) and Burkitt lymphoma (1/15). The overall pooled estimate indicated worse outcomes with higher-risk miRNA profiles (pooled HR 2.34, 95% CI 1.74–3.14; I² ≈ 0%). In AML OS–only sensitivity analysis (3 studies), the pooled HR was 2.15 (95% CI 1.43–3.25; I² ≈ 17%). Circulating miRNAs show promise for prognostication in pediatric hematologic malignancies, but clinical adoption is limited by small cohorts, heterogeneous methods, and incomplete reporting of HRs/CIs. Standardized assays, transparent reporting, and external validation are essential.